Compliance with labor laws in developing countries - Haroon Bhorat; Ravi Kanbur; Benjamin Stanwix (IZA World of Labor, 2019)
Compliance with minimum wage laws and non-wage conditions of employment often depends on labor market specific factors. In developing countries, many workers still earn less than the legal minimum and lack access to mandated non-wage benefits. Enforcement has not kept up with regulation growth and compliance has not been measured from a multidimensional perspective. Such an approach would help to understand the impact of institutional variables and country-specific approaches on the level of labor law violation. The difference between de facto and de jure regulation remains particularly pertinent in countries where compliance is low.
Keywords: E24; J23; J30; J31; J38; 330; legislated minimum wages; developing countries; index of violation; enforcement; compliance; ALMPs